Urban farming as a form of the future food security in the Czech Republic - Jan Szturc; Tomáš Mašíček; Adéla Navrátilová; Jana Kozlovsky-Dufková (Journal of Agriculture, Food Systems, and Community Development)
The article explores alternative ways of utilizing urban spaces for agricultural production, in contrast with permanent land occupation. The primary goal is to highlight the process of urban farming in the Czech Republic, where it is not yet widely practiced. The research component of the study assesses the production potential of newly identified suitable spaces that could partially meet the demand for food. Specifically, the urban farming production potential for vegetables in the city of Olomouc was determined based on currently available data and spatial analysis using ArcGIS Pro software. The results indicate that 408.04 hectares of land currently not used for agricultural activities in Olomouc could be repurposed for urban farming. This total area has a production potential of 7,099.9 tons, which would meet 42.68% of the total demand for vegetables. Given that current knowledge suggests it is not possible to generalize which locations will have high or low production potential, it is always necessary to conduct a detailed analysis of the specific area.